O impacto da variação entre as doses de calcário na distribuição a lanço - Kerber, Leonardo (2016)
The essence of Precision Agriculture is reflected by the adoption of techniques to perform localized treatments providing the nutrients that plants need for their development and expression of the productive potential. A successful application of lime and fertilizers, in fixed or variable rate will depend on properly adjusted and calibrated machines, the physical properties of lime and fertilizer recommendation and well-designed maps. In implementing this study we used a device with volumetric metering system, track-type and mechanism of double-disc broadcaster spreader. The evaluation of application quality was based on the files generated by the controllers, which record information such as the amount applied by comparing methodologies to generate recommendation files. The data show that the same apparatus using the recommendation of different files prepared in the application medium influences the quality. The file contains a smaller pixel size of 3,43 x 3,55 meters, with the variation of liming 9 to 18 kg / ha-1 and a recommendation that uses the equation of a polynomial trendline correlating SMP index with liming t / ha-1 influence on system response time, providing a assertiveness in applying the quality of 98,35%. The file contains a larger pixel size of 6,10 x 5,91 meters, with the variation of limestone dose of 500 to 700 kg / ha-1 and a recommendation based on the estimated values of limestone for every class Index SMP without correlates them has an assertiveness 85,13% in application quality. In general, the results show that an application of corrective or fertilizers is influenced by mechanical issues, the physical quality of products and the generation of implementation files, regardless of recommendation to be followed.